2019
DOI: 10.1038/s41598-019-43238-y
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharides obtained from carrageenans as potential antitumor agents

Abstract: Carrageenans are sulfated galactans found in certain red seaweeds with proven biological activities. In this work, we have prepared purified native and degraded κ-, ι-; and λ-carrageenans, including the disaccharides (carrabioses) and disaccharide-alditols (carrabiitols) from seaweed extracts as potential antitumor compounds and identified the active principle of the cytotoxic and potential antitumor properties of these compounds. Both κ and ι-carrageenan, as well as carrageenan oligosaccharides showed cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…(Zhu et al, 2020). Carrageenan oligosaccharides have been reported many times for their antioxidant activity and potential medicinal value (Sun et al, 2015;Calvo et al, 2019). These oligosaccharides are expected to be used as natural antioxidants to replace synthetic antioxidants that are potential safety hazards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Zhu et al, 2020). Carrageenan oligosaccharides have been reported many times for their antioxidant activity and potential medicinal value (Sun et al, 2015;Calvo et al, 2019). These oligosaccharides are expected to be used as natural antioxidants to replace synthetic antioxidants that are potential safety hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compared with carrageenans, carrageenan oligosaccharides have lower molecular weights, stronger tissue penetration abilities, and more extensive application fields (Sun et al, 2015). Numerous studies have shown that carrageenan oligosaccharides have many biological roles, including antitumor (Calvo et al, 2019), antiviral (Kalitnik et al, 2013), antioxidant (Sun et al, 2010), and immunomodulation activities (Huang et al, 2020). Carrageenan degradation methods include chemical methods, such as acid hydrolysis, that usually do not keep native constituents intact (Hjerde et al, 2017); physical methods that degrade carrageenans mainly by ultrasonic, microwave, or radiation, which do not change the composition and structure of oligosaccharides, but the reaction conditions are difficult to control (Abad et al, 2009); and biological enzymatic methods with carrageenases that degrade carrageenans, which can lead to more efficient production of single stereoisomers, fewer side reactions, and a lower environmental burden (Zhao et al, 2018), and is an ideal way to obtain carrageenan oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Some oligosaccharides are also more cytotoxic than their parent compounds, indicating that a lower molecular weight is one of the factors that improves its cell ability. These results point to the potential use of disaccharide units, such as carrabioses coupled to antineoplasics, to improve their cytotoxicity and antimetastatic properties, and the use of iota -CG as an adjuvant or carrier in anticancer treatments [ 101 ].…”
Section: Bioactive Properties Of Carrageenanmentioning
confidence: 99%
“…Growing body of evidence suggests that these marine carbohydrates can prevent virus attachment, entry and replication [7,8]. In addition to their efficiency demonstrated in many studies, carrageenans are characterized by cost-effectiveness and low toxicity [9,10]. However, it has been reported that both food-grade carrageenan and its oligosaccharide fragments used as antiviral agents are cytotoxic [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%